Relationships among nursing students’ self-concept clarity, meaning in life, emotion regulation ability and depression: Testing a moderated mediation model - Hong, Youjuan; Zhang, Xuan; Wu, Weiwei; Chen, Jingjing; Lin, Yan; Zhao, Junyu; Xiao, Huimin (Frontiers in Psychology, 2022)
Objective Self-concept clarity as an inducing factor of depressive symptoms has been confirmed in previous studies. However, little is known about how and when it induces depressive symptoms in nursing students. The study is to examine the potential mediating role of meaning in life and the moderation of emotion regulation ability in the association between self-concept clarity and depressive symptoms among college nursing students. Materials and Methods A sample of 488 college nursing students participated in this study Southeast China. The Chinese adaptations of Self-concept clarity Scale, Sense of life Scale, Depression scale, Emotion regulation scale were used. Mediation and moderation analyses were carried out in the SPSS macro PROCESS. Results Self-concept clarity was significantly and negatively associated with depression in nursing students, meaning in life had a partial mediating effect on the relationship between self-concept clarity and depression. Furthermore, emotion regulation ability moderated the direct effect of self-concept clarity on depression. Conclusion The findings enrich the knowledge of the mediating and moderating mechanisms to explain the association between self-concept clarity and depression in nursing students. There have been proposed interventions concerning increasing self-concept clarity, meaning in life and emotion regulation ability training which could help help reduce the depression among nursing students.